Specific features of japanese political party system (Journal of Oriental Studies, 2016)
Innovative Japan thanks to the successful modernization of all aspects of life, including politics, has achieved phenomenal success, has become a rich country with high technology and challenged the advanced countries of Europe, despite the fact that once she started to practice the European modelof development. You can not of course exclude the fact that in the case of post-war Japan, certain political institutions and laws were largely imposed on the country due to external circumstances and had a historic break with the traditional culture. However, many aspects of political culture provided the progressive political and economic development of the country. The synthesis of the traditional political culture of Japan with elements borrowed from the West, gave a kind of unique character of the Japanese model. Andtoday the model of political modernization of Japan may well serve as a model and guide for the  modernization of many other countries. This article analyzes the specific features of the Japanese party system, that expressed the phenomenon of “half party system” or “system of 1955”, special factional structure of the ruling party, the role and place of political parties in the government, the phenomenon of “the party of the indifferent, personally oriented electorate and boom” small parties “in the political life of modern Japan.
Keywords: Japan; political parties; specificity; polutorapartiynaya system; factional structure; boom “small parties”